2011
DOI: 10.1116/1.3660699
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition for nanostructured Li-ion batteries

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers)Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 69 publications
2
74
0
Order By: Relevance
“…Despite these effects, the AlF3 growth rate remained constant with different cycle numbers at all temperatures studied (Figure 15b) [156]. ToF-ERDA measurements revealed that the films Similar to the methodology of using TiF 4 or TaF 5 as fluorine sources, Mane et al have reported on the deposition of LiF using LiO t Bu and either WF 6 or MoF 6 as the fluorine source [152]. Film growth took place between 150 and 300 • C, with amorphous films being deposited at the lowest temperature.…”
Section: Ald Of Metal Fluorides Using Metal Fluorides As the Fluorinementioning
confidence: 75%
See 3 more Smart Citations
“…Despite these effects, the AlF3 growth rate remained constant with different cycle numbers at all temperatures studied (Figure 15b) [156]. ToF-ERDA measurements revealed that the films Similar to the methodology of using TiF 4 or TaF 5 as fluorine sources, Mane et al have reported on the deposition of LiF using LiO t Bu and either WF 6 or MoF 6 as the fluorine source [152]. Film growth took place between 150 and 300 • C, with amorphous films being deposited at the lowest temperature.…”
Section: Ald Of Metal Fluorides Using Metal Fluorides As the Fluorinementioning
confidence: 75%
“…LISICON (lithium superionic conductor) materials, on the other hand, are mixtures of lithium silicates or germanates, lithium phosphates or vanadates and lithium sulphates and can produce similar conductivities as the NASICON structures [32]. In addition to these material classes, oxides such as Li 6 BaLa 2 Ta 2 O 12 with the garnet structure have been studied extensively and shown to have reasonable ionic conductivities [31]. Another benefit of the garnet materials is their high chemical stability in contact with the electrodes [32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…ALD is best known for its ability to deposit high-quality, ultra thin conformal films of materials based on alternating dosing of chemical vapors that react with surfaces13141516. ALD ensures control of film thickness at nanometer level.…”
mentioning
confidence: 99%